Protective effect of Eurycoma Longifolia Extract on High-Fat Diet- induced histopathological changes in the Islets of Langerhans and Kidneys of Rats - Al-Ani, Imad M.; Ku-Zaifah, Norsidah; Matloub, Gheed I. (Iraqi Journal of Science, 2024)
Obesity has emerged as public health problems, potentially guiding to many diseases such as diabetes mellitus type 2 and chronic kidney disease (CKD).  The aims of the present investigation were to explore possible protective effect of Eurycoma longifolia (EL) extract on the islets of Langerhans and kidneys of high-fat diet (HFD) fed rats. Twenty four healthy adult male Sprague Dawley (SD) rats were randomized into four groups (n=6) and treated for 12 weeks; normal control (ND) group received only normal diet, Group NDEL was received normal diet and EL, Group HFD received HFD only, Group HFDEL received HFD and EL extracts. The animals were scarified at the end of the 12th week; the kidneys and pancreatic tissues were fixed in 10% formal saline and processed for histological studies.The HFD group revealed hypertrophy of the pancreatic islets with congested blood vessels, vacuolization and injured cells. The kidney sections from the HFD treated group exhibited sever damage in the renal corpuscle and tubules. Treatment with EL extract produced an enhancement in tissue damage produced by HFD feeding in the kidneys and pancreatic islets. These observations confirmed positive valuable outcomes of EL extract against the HFD induced-cellular oxidative injury in the pancreatic islets and the kidneys.